Association of Bacterial Vaginosis and Skin Disorders in Patients with Autoimmune Antibody Positivity - Beksac, Burcu; Donmez, Hanife Guler (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: To investigate the association of bacterial vaginosis and skin disorders in patients with autoimmune antibody positivity. STUDY DESIGN: This retrospective study consisted of 80 patients with autoimmune antibody positivity. All patients were evaluated for the presence of bacterial vaginosis and skin disorders. Cervicovaginal smears were used for the definitive diagnosis of bacterial vaginosis. RESULT: We found bacterial vaginosis in 13.75% (11/80) of the cases. 1 (9.1%) and 10 (90.9%) cases had skin disorders in bacterial vaginosis positive and negative groups respectively (p=0.531). CONCLUSION: There is no relationship between bacterial vaginosis and the presence of skin disorders in patients with autoimmune antibody positivity.